THE CONCEPT OF NATIONAL EDUCATION AND THE CONTENT OF THE PROCESS OF NATIONAL EDUCATION IN THE FAMILY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article is written about the concept of national education and the content of the process of national education in the family. No matter how well-educated people learn universal values, they will always remain representatives of a particular nation. No matter how close the nations are, their representatives will not completely harmonize spiritually. As long as such a nation exists, the unique national methods, content and direction of education related to its spirituality are constantly improving. It should also be mentioned that education cannot remain within the framework of purely national traditions and national experience under any circumstances.